THE EFFECT OF ADDITIVES AND REDUCTORS IN SELECTIVE REDUCTION PROCESS OF LATERITE NICKEL ORE - Fajar Nurjaman; Anis Sa'adah; Achmad Shofi; Wuri Apriyana; Bambang Suharno (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2018)
THE EFFECT OF ADDITIVES AND REDUCTORS IN SELECTIVE REDUCTION PROCESS OF LATERITE NICKEL ORE. Selective reduction of laterite nickel ore followed by magnetic separation was carried out to produce ferronickel products. The effect of adding additives and reductor types in the selective reduction process was studied in this study. Reductors used were anthracite coal and palm shell charcoal with variations of 5 to 15% by weight, while the additive used was sodium sulfate (Na2SO4). The reduction process was carried out at temperatures of 950 ºC, 1050 ºC and 1150 ºC for 60 minutes. The addition of 10% sodium sulfate additives by weight in the reduction process of laterite nickel ore produced higher concentrations of nickel as 6.09%, compared to no additives, i.e. 2.45%. The addition of reductors in the selective reduction process of laterite nickel ore shows that the higher the amount of reductors causes a decrease in the concentrate level of nickel. Furhtermore, the type of reductors used shows that the concentrate from the reduction result using anthracite coal reductor produces higher level of nickel and lower level of iron compared to the use of palm shell charcoal reductor.